Peningkatan Perilaku Perawat Melalui Pengetahuan Dalam Menjalankan Prinsip Pemberian Obat Dua Belas Benar - lilis suryani; Lukman Permana (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2020)
Drug administration is one of the most frequently performed nursing procedures. Care is very important in administering the drug. The behavior of nurses in giving drugs to patients is an action that needs attention for nurses so that patients are safe from actions of errors in administering drugs by paying attention to the principles of drug administration. This study aims to determine the relationship between knowledge and nurses' behavior in administering the twelve correct drugs. This type of research is a quantitative study using descriptive analytical research methods with cross sectional research design. The population of this study were all inpatient room nurses, totaling 152 respondents, so the sample size used was 101 respondents with a proportionate stratified sampling technique through the chi-square test. The results showed that the variable which has a significant significance towards the behavior of nurses in carrying out the principles of giving the medicine is the knowledge factor with a p value of 0.016. It is advisable to the nurses to always update or improve the quality of care, especially regarding the principles of giving twelve correct medicines. Keyword: Knowledge, Behavior, Drug Administration